A Comparison of Performances of Turbines for Wave Power Conversion. (2000) - Setoguchi Setoguchi, T. T.; Takao Takao, M. M.; Kaneko Kaneko, K. K.
Abstract : A number of self-rectifying air turbines for wave power conversion have been proposed so far. This paper shows the comparison of the performances of all these turbines proposed for use in the near future. As a result, the impulse turbine with self-pitch-controlled guide vanes is found to have the best performance.